Ketimpangan Penghasilan Berdasarkan Status Pekerjaan dalam Model Imbal Jasa Pendidikan - Hendajany, Nenny; Rizal, Deden (UI Scholars Hub, 2020)
The study aimed to see income disparities between employment status in return on education from 2000 to 2014 using IFLS data. First, this study analyzes the choice of worker status with the multinomial logit method. Second, this study estimating return on education by entering a correction from the first stage. The results show marginal differences in effects between job status. The smallest return on educational was on the status of self-employed employment, and the biggest was working with the help of permanent workers. Differences return indicate income inequality based on their employment status. Return on education declined from 2000 to 2014.